A arte nos contextos histórico-filosófico e do ensino no Brasil : uma abordagem a partir de aspectos teóricos e das distintas visões da comunidade escolar - Biesdorf, Rosane Kloh (2012)
This study aims to research two main areas: preliminary and in a propaedeutic way, the concept of art in its historical / philosophical trajectory according to authors and artists of significant eras to what one might call as "universal of artistic genre" from Western origin. Therefore, it was chosen not to follow an order of chronological and factual succession, unwound linearly. Initially, it was approached the conceptions of the Greek philosophers Plato and Aristotle in ancient history. Finally, we moved to contemporaneity, where various movements can be seen with a marked feature in common: the loss of work uniqueness, which comes to have various forms and possible readings. Therefore, it was found the foundation in phenomenology of Maurice MerleauPonty, and in the analysis of Pablo Picasso and Marcel Duchamp works. To present the transformations the Art suffered with the rise of the cultural industry, the thought of Adorno, Horkheimer and Benjamin was analyzed. These studies are presented in order to link the historical-social reality, producing artistic and philosophical thinking of each of those periods. The choice of these periods occurred because they are moments of rupture and consequently bring significant changes in society and arts. The second aspect of this research takes into account the reasoning of earlier developed Art concept and problematizes it, when inserting it in the school context. In this regard, initially it was made a historical survey to know the teaching of art in Brazil, and still investigated, on the one hand, the normative aspects that guided the implementation and continuity/discontinuity of Art teaching in Brazil, as well as the theoretical framework that deals with the teaching of art from the Triangular Proposal for Art Education, which aims to address its teaching based on three main axes: contextualization of the work; making art and art appreciation. On the other hand, through empirical research, it was investigated the school community of two schools, one state school and another municipal in São Carlos. It was noticed from the data collected, that the practice of teaching Art is far from the Legal norms laid down in the discipline, but also that this teaching is not contributing to the formation of high individuals as advocated by the philosophers previously studied. It was still evident that there is a mediatic culture which learners are adept of. In practice the teaching of Art is reduced to making art and the students are not getting an education that enables them to understand and appreciate art.